VARIASI BAHASA SISWA DAN SISWI KELAS 8 SMP STRADA MARGA MULIA: KAJIAN SOSIOLINGUISTIK - Wohingati, Angel Cano Abigael; Siagian, Irwan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Abstract The purpose of this research is to describe the form of language variation and the factors behind the emergence of language variation. The language variation referred to in this study is the variety of languages used by 8th grade students of Strada Marga Mulia Middle School in everyday life. This research method uses descriptive qualitative which describes the object naturally. The data collection method used the free-of-conversation (SBLC) method of listening. The listening method is carried out using two techniques, namely tapping and note-taking techniques. The tapping technique is done by tapping, which is recording secretly and the note-taking technique is done to record unclear language in order to make it easier for researchers to describe the data findings. The results of this study found that there are forms of language variation in the form of two languages, namely English and Indonesian. There is also a vulgar form that is often spoken by some people, this is caused by environmental factors. In addition, there are several factors behind the language variation, namely, the area of origin, the relaxed factor, the familiarity factor, and the environmental factor.